Rural winds: struggle, training and popular economy in the face of problematics consumptions (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
The articulation between the educational experience of the Juana Azurduy Training School and a set of university teams from the National University of Luján is part of a work strategy that articulates the substantive functions within the framework of an agreed action. The School is a training space aimed at members of the popular organization Vientos de Libertad (VDL) and a rural productive project. VDL is an organization part of the Excluded Workers Movement, which addresses the problem of consumption,  understanding as emerging from the dynamics of an unequal society. Our support and accompaniment  to the reality under construction has the following tasks: a) liaison with the teams of the technical disciplines to bring them closer to the proposal and collaborate in their implementation, b) coordinate the process of systematizing the experience so that it can be appropriated by other VDL spaces. The work includes a reconstruction of the experience and an analysis of the perspective of the subjects involved.
Keywords: popular economy; social movements; problematic consumption; training; popular education